PENGELOLAAN PARIWISATA PANTAI PULAU DATUK OLEH DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN KAYONG UTARA - Azan Syaputra E.42008069 (FISIP Universitas Tanjungpura Pontianak, 2012)
Based on the problems that occur and are associated with the management of tourismPantai Pulau Datuk Kecamatan Sukadana Kabupaten Kayong Utara, the infrastructure is inadequate,there is no tourism entrepreneurs (investors), and lack of community participation. Thus, this researchaimed to determine the management of tourism Pantai Pulau Datuk conducted by the DinasKebudayaan, Pariwisata, Pemuda dan Olahraga dalam Kabupaten Kayong Utara. Based on the resultsof the research indicate that the management of tourism Pantai Pulau Datuk conducted by the DinasKebudayaan, Pariwisata, Pemuda dan Olahraga dalam Kabupaten Kayong Utara is still in the processof implementation. However, in the implementation of the program, there are still obstacles to beinhibiting the development process in the tourism management. The suggestion from this research thatthe Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kabupaten Kayong Utara did deliberationwith local authorities in managing tourism and find solutions problem existing settlement. Then thenecessary communication and coordination among agencies. Further promotion of flagship programsattractions in phases, in order to attract the attention of many people and tourism entrepreneurs(investors). And socialize on a regular basis about the benefits and management objectives for thetourism Kabupaten Kayong Utara.Keyword : Role, Management of Tourism.